Competitiveness of the Republic of Belarus in international trade of modern knowledge-intensive services - Garbuz, Andrey M.; Grichik, Marina V.; Saikouskaya, Darya A. (Journal of the Belarusian State University. Economics, 2018)
This study analyses competitiveness Republic of Belarus’s trade in modern knowledge-intensive services which compose more than 1/5 of its services exports. The authors compare dynamics and structure of Belarus’ export performance with its neighbor-countries and world leaders based on balance of payments statistics. The paper also examines reasons behind the development of modern knowledge-intensive trade – human capital, infrastructure and institutions – compa ring counties’ rankings in the Global Innovation Index. Moreover, the authors characterize exports development and its prospects of each type of modern knowledge-intensive services. Authors conclude that despite a number of positive trends observed in trade in modern knowledge-intensive service, its results so far are insufficient proceeding from Belarus potential. Because of their low rate of foreign value added, self-sufficiency and relatively high geographical diversification modern knowledge-intensive services can play much bigger role in ensuring trade balance surplus and balance of payments’ sustainability. Therefore, it is necessary to continue work on implementing support measures for export of other business, financial and insurance services, and further develop incentive measures for IT-services.